Study guides

☆☆

Q: How do you solve x squared minus 2x minus 4y squared minus 4y?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

This is a difference of two squares, which factorises to: (3x - 4y)(3x + 4y)

(5x - 2y)(5x + 2y)

x = 2 so x squared = 4 and 2x squared = 2 times 4 = 8; y = 4 so xy = 2 times 4 = 8 and 3xy = 3 times 8 = 24; y squared = 4 times 4 = 16 and 4y squared = 4 times 16 = 64; so 8 + 24 - 64 = 32 - 64 = -32

7(3y-2)-(-4y+9)

2x + 4y = 16 <=> 2x + 4y - 16 = 0 2x - 4y = 0 2x - 4y = 2x + 4y - 16 -8y = -16 y = 2 Substituting the known value for y in either of the original equations enables x to be determined. 2x + (4*2) = 16 : 2x = 16 - 8 : x2x = 8 : x = 4 2x - (4*2) = 0 : 2x - 8 = 0 : 2x = 8 : x = 4. The ordered pair satisfying both equations is (4,2)

Related questions

(y-2) (x+4)

This simplifies to 3x-6+4y.

This is a difference of two squares, which factorises to: (3x - 4y)(3x + 4y)

Isolate one of the variable using inverse operations. Then solve. Example: 2x + 4y = 0 --subtract 4y>> 2x = -4y --divide by -4>> -1/2x = y --plug in your variable -->>

(5x - 2y)(5x + 2y)

2x-4y=-8-2x......-2x-4y=-2x-8(-4y)/-4 | (-2x-8)/-4y=1/2x+2

if you rearrange it, it becomes 4y + 8 = 3x2 -2x +1 4y = 3x2 -2x -7 y= (3x2 -2x -7)/4 which is a parabola

(2y + 3)(2y - 3)

You cannot solve one equation in two unknowns.

4(y - 3)(y + 3)

If you mean: 3+2x = 12 and 4y-x = 5 then their values are x = 4.5 and y = 2.375

(13x^2 - 4y)(2x^2 - 5y)

People also asked